2017
DOI: 10.1002/smll.201702300
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Chalcogenide Nano‐Heteroplatelets: Creating Advanced Nanostructured Materials by Shell Growth, Substitution, and Attachment

Abstract: The current direction in the evolution of 2D semiconductor nanocrystals involves the combination of metal and semiconductor components to form new nanoengineered materials called nano-heteroplatelets. This Review covers different heterostructure architectures that can be applied to cadmium chalcogenide nanoplatelets, including variously shaped shell, metal nanoparticle decoration, and doped and alloy systems. Here, for the first time a complete classification of nano-heteroplatelet types is provided with recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 159 publications
(257 reference statements)
0
24
0
Order By: Relevance
“…For 2D all-inorganic perovskite NPLs, Bekenstein et al first reported CsPbX 3 NPLs showing the 1–5 unit cells thickness in 2015 [141]. Since then, many efforts have been focused on synthesizing precisely tunable as well as uniform CsPbX 3 NPLs [142,143,144,145]. Currently, colloidal NPLs of perovskite metal halides have been found to be a significant family of materials for LEDs, which enriches the diversity of semiconducting nanomaterials and provide a platform for exploring new optoelectronic properties of 2D semiconducting materials.…”
Section: Approaches To Achieve Npl-ledsmentioning
confidence: 99%
“…For 2D all-inorganic perovskite NPLs, Bekenstein et al first reported CsPbX 3 NPLs showing the 1–5 unit cells thickness in 2015 [141]. Since then, many efforts have been focused on synthesizing precisely tunable as well as uniform CsPbX 3 NPLs [142,143,144,145]. Currently, colloidal NPLs of perovskite metal halides have been found to be a significant family of materials for LEDs, which enriches the diversity of semiconducting nanomaterials and provide a platform for exploring new optoelectronic properties of 2D semiconducting materials.…”
Section: Approaches To Achieve Npl-ledsmentioning
confidence: 99%
“…To date, a manifold of ways to modify the NPL structure has already been developed, including the growth of shells, crowns and domains around the core NPLs. 19 Depending on the desired application, the modication material can either be a semiconductor (wide or narrow bandgap) [20][21][22][23][24] or a metal. 25,26 If a shell is grown around a core NPL, the shell material is deposited on all surfaces of the NPL, which results in a lateral extension as well as in an increase in the NPL thickness.…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen, CdS QDs, CdSe/CdS QDs, and CdSe/CdS nanorods were characterized by the presence of PL emission that was not significantly affected by defects states. However, in the case of CdS nanoplates, there was no emission detected, due to typical for this geometry high surface area and a number of defects present at the surface (Tessier et al 2013 The variety of NPs used was confirmed (El-Bially et al 2012;Adel et al 2017;Kormilina et al 2017) by TEM measurements (Fig. 2 A-D).…”
Section: Resultsmentioning
confidence: 77%